DOES ANY RESEARCH GAP ON EDUCATION STARTUP (EDTECH) IN INDONESIA - Yulianto, Harry; Sumardi, Sumardi; Nursyamsi, Idayanti; Pakki, Erlina (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The purpose of this study is to identify research gin on educational stastartups Indonesia. There were five proposed research questions: (RQ1) publication trends; (RQ2) publishers which published the most articles; (RQ3) researcher who was productive; (RQ4) the most cited article titles; and (RQ5) publication network map. The design research was quantitative with a descriptive approach. The research method uses a literature review with bibliometric analysis. The research data was from the Google Scholar database. Data analysis was done using VOSviewer software. The resindicatecates: (1) publications with the theme Education Startup (EdTech) in Indonesia were 49 articles; (2) KhazanahIntelektual was the publisher which publishes the most article on Education Startup (EdTech) in Indonesia; (3) Nurkholifatul Maula was the productive researcher (4 articles); (4) the paper written by Faulinda Ely Nastiti and AghniRizqiNimal Abdu entitled “Indonesian Education Readiness to Face the Era of Society 5.0” was the most cited (261 citations); and (5) there was only one cluster has the opportunity to be a research gap related to Education Startup (EdTech) in Indonesia. The results indicate there was a research gap, so future research has the potential to be renewable research on management science and digital entrepreneurship